Influence of calcium hydroxide as an intracanal medicament on apical leakage following obturation using three different sealers (Bangladesh Journal of Medical Science, 2011)
Background and objectives: The aim of this invitro study was to study the effect of calcium hydroxide when used as an intracanal medicament on apical leakage following obturation using zincoxide eugenol (Tubliseal), calcium hydroxide (Apexit) and glass ionomer (Ketac-Endo) based sealers. Methods: Sixty seven recently extracted human permanent teeth with single roots were selected for the study. To facilitate instrumentation, the crown portion of each tooth was removed at the level of CEJ with a thin diamond disk using slow speed straight hand piece. The canals were prepared using a step back technique and divided into two equal groups of 33 each into group A and group B. One root was used as a positive control group. Group A was medicated with calcium hydroxide for 7 days and Group B was not medicated. Group A and Group B were randomly divided into three subgroups (A1, A2 and A3, B1, B2 and B3) containing 11 roots each, for obturation using three different sealers. A1and B1 was obturated using Tubliseal, A2 and B2 was obturated using Apexit and A3 and B3 was obturated using Ketac-endo. One root in each sub-group was selected and completely coated with nail varnish and used as a negative control. One unfilled root was used as positive control. All the roots were subjected to dye penetration using methylene blue for one week. The roots were longitudinally sectioned and observed under stereomicroscope. Results: The Tubliseal medicated group showed statistically less leakage compared to the nonmedicated group. The Apexit and Ketac-endo group also showed less leakage but were not statistically significant. Interpretation and conclusion: All the medicated groups showed less leakage when compared with the non-medicated group. When calcium hydroxide used as a medicament, there was less leakage. This may be due to effect of residual calcium hydroxide, which was left on the canal walls. Keywords: Medicated; non-medicated; Tubliseal; Apexit; Ketac-Endo. DOI: 10.3329/bjms.v10i1.7317 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.34-40